The Lack of Islamic Religious Education Learning in Fiqh Subjects at Madrasah Aliyah SKB 3 Bingkat - Maharani, Anggi Ditami; Hasan, Ibrahim (Khalifah : Jurnal Pendidikan Nusantara, 2025)
This study aims to examine and analyze the limited learning of Islamic jurisprudence (fiqh) at Madrasah Aliyah SKB 3 Bingkat. Fiqh, as a branch of Islamic science that discusses sharia laws in everyday life, should be a central pillar of religious education. However, observations and interviews indicate that the intensity of fiqh learning at this madrasa remains relatively low, both in terms of teaching time, teacher competence, and learning methods used. Several contributing factors identified include a limited number of competent teachers in fiqh, a lack of relevant teaching materials, and low student interest in the subject. This limited fiqh learning impacts students' poor understanding of Islamic law and its application in daily life. This study recommends improving the quality and quantity of fiqh teaching through teacher training, the provision of engaging learning media, and the integration of active learning methods to increase student participation and understanding.